Letter to the Editor: Botnia Fray Bentos and the environment of Uruguay River basin. The reports of EcoMetrix-World Bank - Matta, Elias Jorge (2009)
The pollution load caused by Botnia Fray Bentos S.A., a Mega Kraft Mills with ECF bleaching, is analysed on the basis of two reports of Eco Metrix at the request o f the International Finance Corporation, World Bank. The first report evaluates the first six months of mill operations, from November 2007 to April 2008 . The second report covers the 12 months of 2008 . Regardless of the opinions expressed by Eco Metrix, from the numerical values shown in the reports it is clear that Botnia has discharged huge quantities of dangerous pollutants into the Uruguay River and into the atmosphere. This pollution load, according to the background known, will cause serious and irreversible damage to the flora, fauna and health of the inhabitants of the basin within a few years. Since the findings of EcoMetrix are in contradiction to the logical analysis of the same values that the consultant presents, a detailed discussion of the criteria and limits (standard) used in the reports is unavoidable.